Perlindungan Hukum Bagi Kreditor Separatis Dalam Pembagian Dan Pemberesan Harta Pailit - Indri Adelia Putri (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Bankruptcy exists to guarantee that creditors obtain the rights attached to them in accordance with statutory regulations, this is in accordance with the main objective of bankruptcy, namely to divide the debtor's assets among creditors to avoid separate executions and inconsistent distribution. in accordance with applicable legal proportionality. The curator is one of the parties authorized to manage and settle bankruptcy assets after the debtor is declared bankrupt. In this process, the curator is supervised by a supervisory judge who is appointed by the Commercial Court Judge at the time the decision to declare bankruptcy is declared to the debtor. The curator is not completely free in carrying out the settlement or distribution of bankruptcy assets, the supervisory judge in this case has the authority to supervise the management and settlement of bankruptcy assets carried out by the curator.